2018
DOI: 10.1021/acsphotonics.8b00186
|View full text |Cite
|
Sign up to set email alerts
|

Multiband Plasmonic Sierpinski Carpet Fractal Antennas

Abstract: Deterministic fractal antennas are employed to realize multimodal plasmonic devices. Such structures show strongly enhanced localized electromagnetic fields typically in the infrared range with a hierarchical spatial distribution. Realization of engineered fractal antennas operating in the optical regime would enable nanoplasmonic platforms for applications, such as energy harvesting, light sensing, and bio/chemical detection. Here, we introduce a novel plasmonic multiband metamaterial based on the Sierpinski … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 45 publications
1
57
0
Order By: Relevance
“…Deterministic fractals 35 are self-similar objects generated by geometrical rules, having a non-integer (Hausdorff-Besicovitch) dimension. Sierpinski carpets can be generated by a recursive geometrical algorithm employing a Lindenmayer system implementation 34 . We designed Au/G SCs starting from a graphene unit cell of side L 0 = 10 μm that is divided into a 3 × 3 array of sub-cells of lateral size L 1 = L 0 3 −1 , with an Au square placed in the central sub-cell.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Deterministic fractals 35 are self-similar objects generated by geometrical rules, having a non-integer (Hausdorff-Besicovitch) dimension. Sierpinski carpets can be generated by a recursive geometrical algorithm employing a Lindenmayer system implementation 34 . We designed Au/G SCs starting from a graphene unit cell of side L 0 = 10 μm that is divided into a 3 × 3 array of sub-cells of lateral size L 1 = L 0 3 −1 , with an Au square placed in the central sub-cell.…”
Section: Resultsmentioning
confidence: 99%
“…We designed Au/G SCs starting from a graphene unit cell of side L 0 = 10 μm that is divided into a 3 × 3 array of sub-cells of lateral size L 1 = L 0 3 −1 , with an Au square placed in the central sub-cell. By iteratively applying the same rule to the generated sub-cells of size = = − L L L 3 t t t 0 0  , it is possible to obtain fractals for higher orders t of complexity 34 . In this way, we indirectly patterned graphene, thereby realizing an Au/G fractal metamaterial that can be thought as a discrete Au SC and a complementary continuous graphene SC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Sierpinski Carpet (SC) fractal structure is one of the self-similar sets, which is fabricated by the technique of dividing a square into some smaller squares, removing one square, and continuing recursively [19]. It is reported that the bandgap in phononic crystals dominating the elastic wave propagation can be changed by conducting the SC fractal structures, which is widely used in the fractal antennas design [20][21][22][23]. Furthermore, the effect of SC fractal structure on the k of the Si/Ge nanocomposites is evaluated by using MD method [24].…”
Section: Introductionmentioning
confidence: 99%